2015
DOI: 10.1080/07448481.2015.1068173
|View full text |Cite
|
Sign up to set email alerts
|

Readjustment of Urban Veterans: A Mental Health and Substance Use Profile of Iraq and Afghanistan Veterans in Higher Education

Abstract: Objective To identify the prevalence of substance use and mental health problems among veterans and student service members/veterans (SSM/V) returning from Iraq and Afghanistan to New York City’s low-income neighborhoods. Participants A sample of 122 veterans attending college and 116 veterans not enrolled recruited using respondent driven sampling. Methods Logistic regression analysis of variation in characteristics of those veterans attending college; linear regression examining effects of college attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Overall, as noted by Aikins et al (2015), African American veterans face greater challenges reintegrating into society and the workforce because of a lack of training and higher education and failure to take part in vocational services programs. Although the New Post-9/11 GI Bill has presented more benefits and opportunities for veterans to receive an education after their transition from the military, African American veterans continue to fail to use their benefits as compared to other veterans (Keillor, 2009).…”
Section: Problem Statement and Purposementioning
confidence: 99%
See 2 more Smart Citations
“…Overall, as noted by Aikins et al (2015), African American veterans face greater challenges reintegrating into society and the workforce because of a lack of training and higher education and failure to take part in vocational services programs. Although the New Post-9/11 GI Bill has presented more benefits and opportunities for veterans to receive an education after their transition from the military, African American veterans continue to fail to use their benefits as compared to other veterans (Keillor, 2009).…”
Section: Problem Statement and Purposementioning
confidence: 99%
“…Furthermore, African American veterans' failure to seek higher education and use their benefits may result from their lack of knowledge about VA education programs and his or her mental status which interferes with performance in higher education settings (U.S. Department of Veterans Affairs, 2017). According to Aikins et al (2015), African American veterans are underrepresented in American higher education and adversely impact the national economic health because of the costs associated with their care. Furthermore, an adverse impact on social equity is also altered for African American veterans.…”
Section: Problem Statement and Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Within institutions of higher education, transitional challenges can include navigation of the governmental and institutional bureaucracies, for example, understanding and application of benefits and support systems; feelings of being overwhelmed and dismayed if not provided mechanisms of support as a result of assimilation (Bonar & Domenici, 2011; Brown & Gross, 2011); social, cognitive, physical, and psychological readjustment challenges when transitioning to college environments (Aikins, Golub, & Bennett, 2015); addressing personal family issues (Johnson et al., 2014); feeling apathetic concerning their future outlook (Pew Research, 2011); lack of patience for ignorant questions related to serving in the military (Doe & Doe, 2010; Rumann & Hamrick, 2009; Sander, 2013; The Institute for Learning Technology 2011); testing and accommodations related to “attention and concentration difficulty, information processing challenges, learning and memory deficits, sluggish or abstract thinking, and slowed executive functions (problem solving, planning, insight, awareness, sequencing” (Connelly, 2012, p. 15); and academic to career transition (Minnis, 2014), and identity issues related to “removal of the forced military identity” as they “struggle to re‐assume roles as civilians” (Baechtold & De Sawal, 2009, p. 40).…”
Section: Transitional Challenges Of Veterans In Higher Educationmentioning
confidence: 99%
“…Veterans may struggle with tinnitus or hearing loss, making listening to classroom lectures and participating in discussions more problematic (Young, 2017). Furthermore, Aikins, Golub, and Bennett (2015) found that many student veterans had a Traumatic Brain Injury (TBI). A TBI may negatively impact attention, cognition, memory, and be accompanied with other physical or mental symptoms (Defense and Veterans Brain Injury Center, 2016).…”
Section: Introductionmentioning
confidence: 99%